Design challenges for embedded based wireless postoperative bedside monitoring system. Issue 1 (2nd January 2020) - Ashisha, G. R.; Anitha Mary, X.; Rose, Lina
Abstract: The monitoring of a patient can be carried out by continually measuring the vital parameters by using a pulse oximeter. SpO2 (Oxygen saturation) and the heart rate are the certain parameters for the critical patients to be monitored continuously. In this monitoring system, parameters of the patient are monitored by using pulse oximeter having two Light Emitting Diodes (LED's) with dissimilar wavelengths. Continuous Pain free monitoring is achieved by a non-invasive monitoring procedure. In this paper, the measured values of SpO2 and the heart rate are wirelessly sent to the doctor through Wi-Fi. These measurements provide early caution to the person to avoid the possible problems in the body.